Distribution of fingerprint patterns among first year medical students in Al-Ameen Medical College, Bijapur - Shamshuddin R. Kakkeri; Habibullah Attar (Al Ameen Medical College, 2017)
Introduction: Fingerprint evidence is undoubtedly the most reliable and acceptable evidence as one of the most mature biometric technologies and are considered to be legitimate proofs of evidence in courts of law for human identification all over the world as they are constant and individualistic Aim: The present study was done to see the pattern of fingerprints among first year medical students. Methods: Study was carried out among 120 first year medical students (60 male & 60 female) belonging to the age group 17-21 years of Al-Ameen Medical College, Bijapur, Karnataka, during the period of 2016-17. Fingerprints of the fingertips were taken using the ink method. Distribution of fingerprint patterns were studied in both hands among males and females and are compared. Results: As finger prints are unique, whorls are the most commonly occurring fingerprint pattern while arches are the least common. Frequency of whorls is comparatively higher and that of loops lower. Conclusion: Different patterns of fingerprints are present in different digits in both males and females.